(untitled) (Research, Society and Development, 2020)
In the hospital environment, the concern about the production of safe meals is bigger, considering that the intake of contaminated food can change the clinical status of patients. The study aimed to evaluate the microbiological quality of milk-based beverages with fruit offered for the patients admitted to a University Hospital in the city of Rio de Janeiro and to well analyze the sanitary conditions of the Food and Nutrition Unit that supply the beverage. The object of the study was a milk-based beverage prepared with the following ingredients: skim milk powder, semi-skim milk, mango and maltodextrin. Salmonella spp./25g, Bacillus cereus, Coagulase positive Sthapylococcus, coliforms at 45oC and total mesophilic aerobic bacteria were analyzed. It was made up and applied a Good Practices Checklist with 68 items divided in 10 blocks that were classified as compliant and no compliant. Of all samples, 40% were not appropriated for the consumption because they had coagulase-positive Sthaphylococcus, coliforms at 45oC and total mesophilic aerobic above the maximum limit established. The checklist, showed that 50% of the blocks had a percentage of compliance less than 70%. Therefore, corrective measures must be taken during the production process in order to guarantee the preparation of safe foods for patients.